The main factors influencing the perception of Singapore youths who consume fashion towards consuming sustainable fashion - Liau, Breanne Wei Qi (Nanyang Technological University, 2024)
The fast fashion industry proves to be a serious global and political issue. With widespread and devasting implications on the well-being of the environment and society, greater action is necessary to drive sustainable consumption. Singapore youths are believed to have an increased awareness and concern for environmental and social issues. However, their sustainable fashion consumption practices remain low. Through conducting qualitative interviews, this study identifies several key factors that shape consumer choices concerning sustainable fashion, which include affordability, style/design, social influence, ability to find what one likes, environmental and social awareness, and awareness about sustainable brands/options. Contributing to the understanding of sustainable consumption, the results can guide policymakers and industry stakeholders in creating a more conducive environment for sustainable practices in the fashion industry.